2016
DOI: 10.1093/mnras/stw2362
|View full text |Cite
|
Sign up to set email alerts
|

The void galaxy survey: photometry, structure and identity of void galaxies

Abstract: We analyze photometry from deep B-band images of 59 void galaxies in the Void Galaxy Survey (VGS), together with their near-infrared 3.6µm and 4.5µm Spitzer photometry. The VGS galaxies constitute a sample of void galaxies that were selected by a geometric-topological procedure from the SDSS DR7 data release, and which populate the deep interior of voids. Our void galaxies span a range of absolute Bmagnitude from M B = −15.5 to M B = −20, while at the 3.6µm band their magnitudes range from M 3.6 = −18 to M 3.6… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 96 publications
1
26
0
1
Order By: Relevance
“…6, bottom panel). Without trying to over interpret these results given the fact the general galaxy population in voids consists of mostly small late-type spirals and massive ETGs are very rare (Croton et al 2005;Beygu et al 2017), the above findings suggest that DM haloes of ETGs are less dense when these objects live in low-density regions, even if more extended kinematic data are needed to confirm this, given the large errors affecting our DM densities. The same remark applies to the reported DM fractions, which are similar to the ones derived for cluster ETGs (see Table 5).…”
Section: Discussionmentioning
confidence: 80%
“…6, bottom panel). Without trying to over interpret these results given the fact the general galaxy population in voids consists of mostly small late-type spirals and massive ETGs are very rare (Croton et al 2005;Beygu et al 2017), the above findings suggest that DM haloes of ETGs are less dense when these objects live in low-density regions, even if more extended kinematic data are needed to confirm this, given the large errors affecting our DM densities. The same remark applies to the reported DM fractions, which are similar to the ones derived for cluster ETGs (see Table 5).…”
Section: Discussionmentioning
confidence: 80%
“…In this study, we explored the properties of the isolated quiescent galaxies in the void environments. Previous works have already shown that void galaxies tend to be bluer and have a statistically higher fraction of the late-type galaxies compared to the average galaxy environments (e.g., Rojas et al 2004Rojas et al , 2005Hoyle et al 2012;Kreckel et al 2012;Liu et al 2015;Beygu et al 2017). We have shown that the total fraction of the quiescent galaxies in the void regions is about ∼ 18% down to a limiting magnitude of -19 in the r-band, and the fraction of the isolated quiescent ones is ∼ 14%.…”
Section: Discussionmentioning
confidence: 97%
“…Voids also present a useful probe to understand the nature of galaxy formation. It is known that galaxies found in voids are typically spiral/irregularly-shaped and found to be HI rich, having low luminosity and stellar mass, and small size relative to the general population of galaxies (Tavasoli et al 2015, Beygu et al 2017, and Pustilnik et al 2019). This suggests that galaxy formation and evolution may have a dependence on the large scale dark matter density.…”
Section: Introductionmentioning
confidence: 99%